PENGARUSUTAMAAN GENDER DALAM PROGRAM GERBANG HEBAT SEBAGAI STRATEGI PENGENTASAN KEMISKINAN DI KOTA SEMARANG - Landung Esariti; Lillah Haulah; S Sunarti (Diponegoro University, 2019)
The purpose of gender mainstreaming is to ensure that access, participation, benefits and control by men and women at the individual and household levels are well accommodated. As one of the national development principles, gender must be integrated in sectoral development including efforts to reduce poverty at the City / District level. This trigger the need to research on whether the Gerbang Hebat program initiated since April 2016 has succeeded in implementing gender-based program planning. Based on the results of the quantitative approach in structured interviews with 16 respondents representing 12 government agencies in Semarang City, the following findings were obtained. There is a merit in the context of comparisons between the purpose of the Gerbang Hebat with gender mainstreaming objective. A deeper examination of the suitability of the Gerbang Hebat as a poverty reduction strategy found a less insufficiency. Although in principle, the implementation of the Gerbang Hebat has included key variables, namely (a) opportunity provision, (b) capacity building, (c) security and (d) community empowerment. However, there is a need to strengthen understanding of the gender context at the program planner level. Specifically, program planners should be more sensitive to varying programs to provide opportunities for better quality of life improvement activities, as the final objective of all poverty alleviation programs.